'Four Seasons Fill the Measure of the Year': Romantic Meteorology. (2nd January 2021) - Doyle, Sarah
ABSTRACT: This essay offers a critical appreciation of the occurrence and function of meteorological language and imagery in selected Romantic poetry. Focusing on individual poems by Wordsworth, Coleridge, Clare, Keats and Shelley, I examine the ways in which weather writing in these examples may transcend the observational and become experiential, with weather conditions being a vehicle by which personal concerns can be articulated in a conflation of the external and the internal.